2004
DOI: 10.1038/sj.bjc.6601693
|View full text |Cite
|
Sign up to set email alerts
|

Trends in postoperative radiotherapy delay and the effect on survival in breast cancer patients treated with conservation surgery

Abstract: The adequate timing of adjuvant radiotherapy (RT) in breast cancer has become a subject of increasing interest in recent years. A population-based study was undertaken to determine the influence of demographic and clinical factors on the postoperative RT delay in patients treated with breast-conserving surgery (BCS) and to assess the impact of delay on survival. In total, 7800 breast cancer patients treated with BCS and adjuvant RT between 1986 and 1998 in Yorkshire were included in the study. The median inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
63
0
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(66 citation statements)
references
References 21 publications
1
63
0
2
Order By: Relevance
“…Thus, the delay between surgery and RT was longer (at least 8 weeks after the end of CT). Although this delay may account to some extent for the low reconstruction failure rate, it could also jeopardize the carcinogenic efficacy of irradiation [19].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the delay between surgery and RT was longer (at least 8 weeks after the end of CT). Although this delay may account to some extent for the low reconstruction failure rate, it could also jeopardize the carcinogenic efficacy of irradiation [19].…”
Section: Discussionmentioning
confidence: 99%
“…An additional advantage of ELIOT is that there is no delay in administering RT in cases that need adjuvant anthracyclines. There is evidence that the delay might increase the risk of local recurrences [30][31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…Mikeljevic et al (2004) found that the mean interval between conservative breast surgery and radiotherapy increased from 5 to 12 weeks over a 10-year period from the late 1980s to the late 1990s. Factors likely to contribute to this effect include availability of trained staff and equipment and increases in workload due to either an increased incidence of cancer or changes in the management of tumours over time, with larger numbers being referred for radiotherapy.…”
Section: Waiting Times For Radiotherapy D Robinson Et Almentioning
confidence: 99%
“…A recent study by Mikeljevic et al (2004) found an increased relative risk of death in breast cancer patients treated with conservative surgery who subsequently waited longer than 9 weeks for radiotherapy. Likewise, there is some evidence that a longer wait for postoperative radiotherapy adversely affects survival for patients with head and neck cancers, small-cell-lung cancer and high-grade gliomas (Seel and Foroudi, 2002).…”
mentioning
confidence: 99%